Exploring condensable organic vapors and their co-occurrence with PM2.5 and O3 in winter in Eastern China. Issue 2 (20th January 2023) - Liu, Yuliang; Liu, Chong; Nie, Wei; Li, Yuanyuan; Ge, Dafeng; Chen, Liangduo; Zhu, Caijun; Wang, Lei; Zhang, Yuxuan; Liu, Tengyu; Qi, Ximeng; Wang, Jiaping; et al.
Abstract : The strongest formation of oxygenated organic molecules occurs when PM2.5 and O3 are co-enhanced. Abstract : Oxygenated organic molecules (OOMs) are important oxidation products of volatile organic compounds (VOCs), and they act as key condensable vapors for new particle formation (NPF) and secondary organic aerosol (SOA) in the atmosphere. However, the large diversity and extremely low concentration make OOMs unmeasurable by conventional means, resulting in a poor understanding of OOMs, especially their formation. Herein, we observed OOMs with state-of-the-art mass spectrometry in a megacity in eastern China during the winter and characterized them by performing positive matrix factorization on binned mass spectra (binPMF). The binPMF analysis revealed 3 factors with clear precursor profiles (1 aromatic and 2 aliphatics), 2 ozone-related factors, 2 mixed-precursor-derived factors with unclear processes, and 4 factors dominated by nitrated phenols. We performed peak assignment on binPMF factors and identified over 1500 molecules with a mean total concentration of 4.7 × 10 7 molecules per cm 3 with all nitrated phenols excluded. Most OOMs are organic nitrates produced by the oxidation of anthropogenic VOC with interactions between the derived RO2 and NO x . These molecules containing 3 to 7 effective oxygen atoms (excluding –NO2 in the nitrate moiety) introduced by autoxidation and multigenerational oxidation are less volatile, and hence, are susceptible to condensational loss. However, the observed OOM concentrations increase with the buildup of PM2.5 . This can be explained by enhanced OOM photochemical production owing to accumulated VOCs and sustained oxidants that outcompete condensational loss. This suggests favored SOA production via OOM condensation during haze. Furthermore, the highest OOM concentrations occur when PM2.5 and O3 are coenhanced. Under this condition, OOMs mainly come from ozone-related factors that are generated jointly with ozone and from aliphatic-dominated factors that are closely associated with PM2.5 . Overall, our results improve the understanding of OOM formation and its impact on the polluted atmosphere.